2018
DOI: 10.1063/1.5010942
|View full text |Cite
|
Sign up to set email alerts
|

Franz-Keldysh effect in epitaxial ZnO thin films

Abstract: Photoconductance spectroscopy has been studied in epitaxial ZnO thin films with different thicknesses that range between 136 and 21 nm. We report a systematic decrease in photoconductivity and a red shift in band edge photoconductance spectra when the thickness is reduced. For thinner films, it is found that the effective energy gap value diminishes. By time dependent photoconductivity measurements, we found an enhanced contribution of the slow relaxation times for thicker films. These effects are interpreted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 39 publications
(48 reference statements)
3
29
0
Order By: Relevance
“…Generally, for the traditional semiconductors (e.g., ZnO, GaN, and GaAs), the external EF gives rise to the decreased PL intensity due to the reduced overlap of electron–hole wavefunction, known as the F‐K effect. [ 1 ] The F‐K effect would also lead to the reduction of the optical bandgap as the EF tilts the conduction and valence band alignment. [ 2 ] Figure S6, Supporting Information, shows the PL spectral changes of the CsPbBr 3 nanoplatelets under different EFs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, for the traditional semiconductors (e.g., ZnO, GaN, and GaAs), the external EF gives rise to the decreased PL intensity due to the reduced overlap of electron–hole wavefunction, known as the F‐K effect. [ 1 ] The F‐K effect would also lead to the reduction of the optical bandgap as the EF tilts the conduction and valence band alignment. [ 2 ] Figure S6, Supporting Information, shows the PL spectral changes of the CsPbBr 3 nanoplatelets under different EFs.…”
Section: Resultsmentioning
confidence: 99%
“…For traditional II–VI and III–V semiconductors with mainly covalent bonding, the applied electric field typically gives rise to the decreased light emission intensity and the red‐shift of the optical bandgap or absorption edge due to the band tilting and reduced overlap of the electron–hole wavefunction, which is termed as Franz−Keldysh (F‐K) effect. [ 1,2 ] The electric modulated optical signal has been widely employed in optoelectronic applications, such as optical switches and sensors.…”
Section: Introductionmentioning
confidence: 99%
“…These predictions are based on the fact that zinc (Zn) is an earth-abundant material; the exciton binding energy of ZnO are unusually high (about 60 meV), and the bandgap energy is around 3.4 eV [81] . From another point of view, it is well known that an internal electrical field can reduce the effective bandgap energy, a phenomenon referred to as the Franz-Keldysh effect [82,83] . Bridoux et al have demonstrated that this effect can be intensified when a tensile strain is generated in ZnO thin films [84] .…”
Section: Introductionmentioning
confidence: 99%
“…X-ray diffraction patterns were performed using CuKα radiation (λ = 0.15406 nm) of a Panalytical-Empyrean system. The results show that the films grew epitaxially in the [0001] direction 19 . From the Kiessig fringes observed in the low-angle θ − 2θ scan 19 , a thickness value of t ≃ 54 nm was determined.…”
mentioning
confidence: 99%
“…In this regard, photoconductivity provides information about intrinsic point defects through their role as carrier traps or recombination centers [13][14][15][16] . Additionally, photoconductance spectroscopy is a suitable tool to extract the effective energy gap E G (defined as the band to band transition of the conducting photoelectrons), which can be modified by band bending in nano-structures, according to the Franz-Keldysh effect [17][18][19] . By means of XPS, previous reports have studied the modification of the band bending properties of ZnO crystals 9,20 or thin films 21 using thermal annealing above ∼ 500 • C. At such a high temperature, the defect structure can be modified and it is difficult to discern its contribution to the band bending from that of the adsorbed species.…”
mentioning
confidence: 99%